Poverty, wealth and ecology – A theological perspective - Bedford-Strohm, Heinrich (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Reflecting on poverty, wealth and ecology – and connecting it with a call for social and environmental transformation – demands an understanding of the present and at the same time a vision of a transformed future. For this reason this the essay takes as point of departure a fictitious newspaper report on a conference in 2100 that reflects on the history of the world over the past century, a history of exploding globalization, economic injustice, massive growth in the divide between rich and poor and increased ecological degradation. All of this, according to the report, lead to a gradual global change in consciousness and efforts to address these challenges to make the twenty-first century an age of global transformation towards a true “world society”. In light of this fictitious future, our societies, but especially also our churches, and where they find themselves today are reflected upon. Then some of the sources we come from, beginning with the Bible and continuing onto some of the rich traditions of our churches is followed by an appeal for overcoming certain false alternatives in how we as churches act in a developing global civil society.